Janus kinase inhibitors – a role for the treatment of cutaneous T-cell lymphomas? - Sarah E. Packer; Patrick M. Brunner (Oncology Reviews)
Despite increases in prevalence, many cutaneous T-cell lymphoma (CTCL) patients still lack effective and safe therapies for their disease. The most prevalent subtype, mycosis fungoides is usually managed with skin directed treatments in early stages, while advanced stages are often targeted with systemic medications. These treatments are all symptomatic except for allogeneic hematopoietic stem cell transplantation, which is associated with its own risks of relapse and potentially fatal complications. A novel class of drugs termed “JAK inhibitors” (JAKi) has recently been developed primarily for chronic inflammatory diseases, but there is substantial evidence of JAK/STAT pathway overactivation also in CTCL. As of 1 December 2024, 14 JAKis have been collectively approved by the European Medicines Agency, the Food and Drug Administration and the Pharmaceutical and Medical Devices Agency of Japan. Despite some evidence from case reports, the efficacy and safety of JAKi in CTCL remains to be determined in controlled clinical trials. This review summarizes the current evidence on pathogenic JAK activation and its potential therapeutic inhibition in CTCL.